PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PAI DI SMP NEGERI 4 LHOKSEUMAWE - TARMIZI TARMIZI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
One of the reasons for the low learning outcomes of students in Islamic Religious Education (PAI) is that the learning model used by the teacher is not appropriate, the teacher carries out learning with a conventional one-way model, only transferring information from the teacher to students. Such a strategy makes students quickly bored and boring. Therefore, teachers need to apply appropriate learning models to be able to stimulate students to learn actively, creatively and innovatively, so as to improve their learning outcomes. This study was designed to conduct research on the use of discovery learning models in improving student learning outcomes on the material